A reserva da intimidade nas interceptações telefônicas frente aos limites hermenêuticos no Estado Democrático de Direito - Tasoko, Marcelle Agostinho (2013)
The scope of this study is to analyze the principle of intimacy, privacy, and inviolability of telephone communications, which are constitutionally protected as fundamental rights, such protection should be guided by the constitutional foundation of human dignity. However, given that there are no absolute rights, the Constitution of the Federative Republic of Brazil in 1988, brings the possibility of restricting such rights through the interception of telephone communications in cases of investigation or criminal. Thus, in 1996, was positively valued specific legislation to regulate the restriction of these constitutional principles. Faced with the social development, some cases of wiretapping began to occur without due regard to legal parameters, leading to the need for the judiciary to weigh the rights involved in each case, through the flexibility of fundamental rights. Thereby, to justify judicial decisions, the Superior Courts started to use the Constitutional hermeneutics, based on general theories of law, to conform the application outside the legal limits, allowing for a possible legal uncertainty on this theme. Therefore, this study seeks to reflect what limits must parameterize the judiciary in relation to interception of telephone communications